IMPACT OF COVID-19 PANDEMIC ON PHYSICAL AND MENTAL HEALTH OF SCHOOL GOING CHILDREN IN U.T. CHANDIGARH - Singh, Amandeep (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Concepts of what constitutes a happy childhood have been upended by the COVID-19 pandemic, which has been both a health and a social crisis for children. The pandemic's long-term impacts on children, their families, and communities are yet unknown. The objective of this paper was to examine the multifaceted impact of lockdown during the COVID-19 pandemic on the health and welfare of children. The study not just tried to understand the negative aspect of lockdown but also looked into the positive aspect that these children felt while they got a lot of time to spend with their family members.